Instrumental and Hedonic Motives for Emotion Regulation in Musical Practice - Breaden Madden, Gerard; Jabusch, Hans-Christian (Frontiers in Psychology, 2021)
Background and study aim: Emotion regulation literature often emphasizes that individuals regulate their emotions for hedonic reasons. However, there is increasing support for an instrumental approach to regulation, in which emotions are regulated if believed to be beneficial to the pursuit of personally relevant goals. When pursing a long-term goal, an individual may delay immediate, hedonic emotional reward in order to maximize the instrumental benefits of emotions. The current study investigates emotion regulation in musical practice, to examine whether musicians adopt specific, regulated emotional stances supporting their goal orientation, and in line with their beliefs about the utility of emotion. Method: Via an online questionnaire, four hundred and twenty-one musicians reported their goal-orientation, meta-emotion beliefs, affect-regulation strategies, and completed a scale assessing the specific emotions they may seek to regulate in order to support musical practice. Data were examined using MANOVA and subgroup analysis. Results: Musicians used affect-improvement strategies more often than affect-worsening strategies in their musical practice. Greater use of affect-worsening strategies was associated with stronger meta-emotion beliefs supporting the utility of unpleasant emotions (F = 30.33; p < .01; ηp2 = .06). Musicians who strongly endorsed this belief showed greater pursuit of mastery goals than goals concerning enjoyment. An examination of specific regulated emotions to support musical practice indicated that, generally, musicians sought to reduce unpleasant emotions, instead preferring to experience pleasant, energetic emotions. However, a subgroup of musicians strongly oriented towards mastery goals may seek a mixed emotional state, increasing anger and nervousness in addition to a range of pleasant emotions (Wilks λ1,420 = 14.42; p < .01; ηp2 = .50). Conclusions: Musicians who pursue mastery may be motivated to experience emotions that combine instrumental and hedonic emotion benefits. Instrumental emotion benefits may be less relevant for musicians who practice for enjoyment. In the interest of providing appropriate guidance to music students, it is a matter of importance to more clearly understand the outcomes that may be associated with the use of affect-worsening strategies, and selecting to experience unpleasant emotions. Research in this field may equip musicians with novel skills for better pursuit of their practice goals.